1981
DOI: 10.3758/bf03332918
|View full text |Cite
|
Sign up to set email alerts
|

Mitral cell responses to the odors of reward and nonreward

Abstract: The purpose of this investigation was to determine if there were specific odor components in the goalbox of a straight alleyway following reward and nonreward trials. Behavioral research has convincingly demonstrated that, unless the goal box is cleaned between animals, a pattern of slow running on nonreward trials and fast running on reward trials soon develops. It has been proposed that the rat emits an odor in the goalbox following nonreward which allows following conspecifics to predict the upcoming goal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
7
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…At present , data in this research area (e.g., Pitt , Davis, & Brown, 1973) suggest that such odors are at least partially airborne. However, despite verification of R and N odors via single-cell recordings from mitral cells in the olfactory bulb (Voorhees & Remley, 1981) , their exact chemical structure and anatomical locus have yet to be determined.As suggested, when rats are tested under odormaximizing conditions, odors will theoretically accumulate as additional subjects are tested. This prediction was recently verified by Prytula, Davis, and Fanning (1981).…”
mentioning
confidence: 99%
“…At present , data in this research area (e.g., Pitt , Davis, & Brown, 1973) suggest that such odors are at least partially airborne. However, despite verification of R and N odors via single-cell recordings from mitral cells in the olfactory bulb (Voorhees & Remley, 1981) , their exact chemical structure and anatomical locus have yet to be determined.As suggested, when rats are tested under odormaximizing conditions, odors will theoretically accumulate as additional subjects are tested. This prediction was recently verified by Prytula, Davis, and Fanning (1981).…”
mentioning
confidence: 99%
“…The "food vs. no food" hypothesis elaborated by Voorhees and Remley (1981) as an alternative to a "frustration odor" interpretation, though not addressed to the Davis et al results, could be construed as compatible with them. They suggested that a rat may emit an "ethologically significant odor (pheromone) when encountering food, thereby signaling the location of food to conspecifics," and that "when encountering food stimuli ... , but no food, the rat emits a pheromone signaling 'food is no longer at this location' to conspecifics" (p. 169).…”
mentioning
confidence: 59%
“…The expression "frustration odor" is probably best reserved for the former of these possibilities, but clearly the second possibility (perceived quantity discrepancy) is not ruled out by the present data, despite the use for convenience of the expression "frustration odor." The distinction between these two mechanisms, expressed by Voorhees and Remley (1981) in slightly different language, may be reflected in ethological functioning, that is, in the reactions of conspecifics to the emitted odors. Presumably, rather different effects might be expected, with that of a true frustration odor perhaps extending to general aggregation and social interaction, and that of a signal of relative food abundance restricted to foraging.…”
mentioning
confidence: 99%
“…Electrophysiological recordings of mitral cells in the rat's olfactory bulb have verified the existence of such proposed Rand N odors (Voorhees & Remley, 1981). Davis, Nash, Anderson, and Weaver (1985) have suggested the integration of this body of odor research within the context of optimal foraging theory (e.g., Charnov, 1976;Krebs, Houston, & Charnov, 1981;Mellgren, 1982;Mellgren, Misasi, & Brown, 1984).…”
mentioning
confidence: 99%